Analisis kemampuan kognitif terhadap kreatvitas Pada era digitalisasi - Arestya, Deassy; Mukhtar, Mukhtar; Anwar, Kasful; MY, Mahmud; Asrulla, Asrulla (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This paper delves deeply into the analysis of cognitive ability concerning creativity in the era of digitalization. Creativity involves a series of complex cognitive processes, including associative thinking, problem-solving, memory, and decision-making. The brain's ability to process information efficiently and in various ways plays a significant role in creativity. Objective national conditions, global challenges, technological challenges, and the use of technology, such as artificial intelligence, often involve ethical issues that can affect creativity, especially in the current era of digitalization. Therefore, the relationship between cognitive ability and creativity is very close, and they mutually influence each other in various aspects. Creativity often involves the ability to process information effectively. Cognitive functions, such as attention, memory, and problem-solving, play a crucial role in processing the information needed to create new ideas. The integration of human cognitive skills and technological capabilities can create a strong combination to enhance creativity. Creativity arising from the understanding and wise utilization of technology can bring significant innovation. By combining cognitive potential and digital tools, individuals can explore creative spaces and address the challenges that arise in the era of digitalization.